Modifying Taylor reaction functions in presence of the zero-lower-bound: Evidence for the ECB and the Fed - Ansgar Belke; Jens Klose (Research On Money in the Economy (ROME), 2012)
We propose an alternative way of estimating Taylor reaction functions if the zero-lowerbound on nominal interest rates is binding. This approach relies on tackling the real rather than the nominal interest rate. So if the nominal rate is (close to) zero central banks can influence the inflation expectations via quantitative easing. The unobservable inflation expectations are estimated with a state-space model that additionally generates a time-varying series for the equilibrium real interest rate and the potential output - both needed for estimations of Taylor reaction functions. We test our approach for the ECB and the Fed within the recent crisis. We add other explanatory variables to this modified Taylor reaction function and show that there are substantial differences between the estimated reaction coefficients in the pre- and crisis era for both central banks. While the central banks on both sides of the Atlantic act less inertially, put a smaller weight on the inflation gap, money growth and the risk spread, the response to asset price inflation becomes more pronounced during the crisis. However, the central banks diverge in their response to the output gap and credit growth.
Keywords: E43; E52; E58; 330; Zero-lower-bound; Federal Reserve; European Central Bank; equilibrium real interest rate; Taylor rule